Penyelidikan Eksperimental Alat Pengisi Daya Menggunakan Termoelektrik Dengan Pemanfaatan Panas Knalpot Sepeda Motor - Wiranata, Rizki; Idris, Muhammad (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2023)
Thermoelectricity is a material that can convert heat energy into electrical energy. By installing a thermoelectric near the exhaust pipe, the heat emitted from the exhaust pipe will automatically be converted into electrical energy. This article discusses the testing of a power charging device that utilizes the heat from the vehicle's exhaust pipe, according to specific requirements. The process begins with the selection of materials and dimensions, followed by design, fabrication, assembly, and performance testing of the power charging device for mobile phones using the heat from the vehicle's exhaust pipe. The objective of this research is to create a device for charging mobile phones or power banks while analyzing the heat generated by the temperature changes. The methodology employed in this study includes experimental setup, device assembly, device testing, and device analysis. The results of the fabrication of the mobile phone charging device using rectangular copper specimens with dimensions of 80 mm in length, 40 mm in width, and 40 mm in height, along with four square-shaped Peltier modules measuring 40 mm x 40 mm x 4 mm each, indicate a voltage output of approximately ±1.5V per Peltier module. The analysis of the heat generated by the temperature changes during testing at 5000 rpm in an idle state resulted in a temperature difference (∆T) of 208.2 K. The voltage produced was 6.06 V, the current was 0.223 A, and the power was 1.35 watts. Testing the engine at 5000 rpm resulted in an electric current of 0.25 A and power output of 1.55 watts. The overall heat transfer rate was U = 23.915 W/℃, and the thermal resistance rate was ΣR = 20.433 oC/W.